Diketopiperazine Cyclo-(S-Pro-R-Leu) Produced by Periconia pseudobyssoides K5 Isolated from Toona sureni (Meliaceae) and its Heme Polymerization Inhibition Activity - Azhari, Azmi; Harneti, Desi; Wulandari, Asri Peni; Mulyani, Yeni; Purbaya, Sari; Sari, Aprilia Permata; Pratama, Galih Bayu; Supratman, Unang; Shiono, Yoshihito (UI Scholars Hub, 2023)
Fungi endophytes are living microorganisms colonizing inside the internal tissue of a plant and provide ecological benefits for their host. Endophytes provide various metabolites for plant adaptation toward biotic and abiotic stresses and have tremendous pharmacological activities. Toona sureni (T. sureni) (Meliaceae) belongs to the Toona genera and is reported to have antimalarial activity. To determine the compounds produced by the endophytic fungus from this plant, we isolated a compound from Periconia pseudobyssoides (P. pseudobyssoides) K5 endophytes from the stem bark of T. sureni. Diketopiperazine cyclo-(S-Pro-R-Leu), a non-ribosomal peptide, was isolated from brown rice fermented at 28 ± 2 ℃ for 30 days. The structure was determined by spectroscopic methods including fourier-transform infrared spectroscopy, mass spectrometry, and 1D and 2D nuclear magnetic resonance techniques. This compound was evaluated for heme polymerization inhibition activity (HPIA) with an IC50 value of 9.89 ± 0.24 mmol/L compared with positive control chloroquine phosphate with an IC50 value of 3.08 ± 0.58 mmol/L. This compound has been categorized as having low activity three times lower than positive control chloroquine phosphate. This information provides new leads about the compound diketopiperazine cyclo-(S-Pro-R-Leu) produced by P. pseudobyssoides K5 endophytes having low activity in inhibiting heme polymerization. In the future, to explore the potency of this compound as antimalarial agent, the other antimalarial test such as lactate dehydrogenase assay might be useful.